The Influence of the Faith Development Program on the Religiosity of Multicultural Students at SMPK Santo Yusup Sumenep Madura - Khadijah; Nazlah Hidayati (Maklumat: Journal of Da'wah and Islamic Studies, 2025)
The faith building program is a spiritual extracurricular that is carried out outside class hours as a forum for students to receive intense religious education services. SMPK Santo Yusup Sumenep is a multicultural educational institution that implements a faith development program as an alternative to equalizing religious services for non-Catholic religious students, with the aim of forming a religious person even though they live in a predominantly Catholic area. Religiosity cannot be separated from various internal policies and the internalization of religious norms and teachings, this makes the faith building program very crucial in shaping an individual's religiosity. Religiosity among pluralities is a unique thing to research so researchers want to know whether there is an influence of the faith building program, if there is any, how much influence the faith building program has on the religiosity of the multicultural students of SMPK Santo Yusup Sumenep. In this research, researchers used a quantitative research method using a data collection technique in the form of disseminating questionnaires regarding variables X and Y, with a population of 22 respondents. The data analysis used is a simple linear regression test. The research results show that the faith development program has a positive and significant effect on the religiosity of multicultural students. This is proven by the results of the t test which shows that thitung > t table (80,642 > 2,086 ) and sig. 0.000<0.05. So Ha was accepted and Ho was rejected. Based on the results obtained, it can be concluded that partially the faith development program has an effect of 99.7% while the remaining 3% is from variables other than the variables studied.